2001
DOI: 10.1021/la0017781
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Surface Hydrophobicity on Adsorption and Relaxation Kinetics of Albumin and Fibrinogen:  Single-Species and Competitive Behavior

Abstract: This work compares the spreading and relaxation rates of albumin and fibrinogen, inferred from singlecomponent and competitive adsorption kinetic experiments, on model surfaces of varying hydrophobicity. Kinetics from the single-component studies revealed a constant spreading rate, where the adsorbed protein footprint grew linearly in time for at least 15 min. This spreading rate increased with substrate hydrophobicity (ranging from 0.02 to 0.16 nm 2 /molecule/s for albumin and from 0.04 to 0.26 nm 2 /molecule… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

41
354
6
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 335 publications
(402 citation statements)
references
References 66 publications
41
354
6
1
Order By: Relevance
“…With contact angle measurements it was shown that titanium is less hydrophilic than mica. In previous studies [19] it has been shown that the more hydrophobic the surface becomes, the stronger the interaction is between the surface and the proteins. This would cause a larger spread of the protein on the surface and thus result in a larger perturbation of the native structure of the protein.…”
Section: Afmmentioning
confidence: 98%
See 1 more Smart Citation
“…With contact angle measurements it was shown that titanium is less hydrophilic than mica. In previous studies [19] it has been shown that the more hydrophobic the surface becomes, the stronger the interaction is between the surface and the proteins. This would cause a larger spread of the protein on the surface and thus result in a larger perturbation of the native structure of the protein.…”
Section: Afmmentioning
confidence: 98%
“…It has been suggested [19,20] that the diminution of the height dimensions upon adsorption is due to rapid spreading of the single molecules immediately after adsorption on the surface. In order to verify whether the small ex situ heights on both mica and CP Ti are mainly due to the spreading during the adsorption process, in situ AFM measurements were performed.…”
Section: Afmmentioning
confidence: 99%
“…Such limitations can lead to misinterpretations of apparent interfacial phenomena, which are used to explain the biocompatibility of biomaterials. For example, conventional biophysical methods often find that the average surface protein conformation relaxes from native-like to nonnative-like upon surface adsorption, which is interpreted as evidence for unfolding (11)(12)(13)(14). However, the time scales over which these conformational changes reportedly occur are orders of magnitude longer than typical surface residence times of isolated proteins (15), suggesting that the picture of surfaceinduced spreading may be oversimplified.…”
mentioning
confidence: 99%
“…Sit et al suggested that the spreading of FG increases with the hydrophobicity of the surface (Sit & Marchant, 1999). In addition, Wertz and Santore have shown through total internal reflection fluorescence that the footprint of a FG molecule is larger when adsorbed on a hydrophobic surface (graphite) than on a hydrophilic one (mica) (Wertz & Santore, 2001;Wertz & Santore, 2002). However, other authors have found the trinodular conformation both on graphite and mica (Agnihotri & Siedlecki, 2004).…”
Section: Tissue Engineering 80mentioning
confidence: 99%